Hubungan Keterpaparan Gadget dengan Pola Makan, Daya Ingat, dan Aktivitas Fisik Anak Sekolah Dasar - Zakiyatul Fikriyah; Anna Noordia; Awang Firmansyah; Anindya Mar’atus Sholikhah (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
The development of information technology that is booming in Indonesia makes a lot of people interested in using gadgets, especially among school-age children. The existence of positive and negative impacts caused by the use of gadgets becomes a warning to always be vigilant in using gadgets. The study was motivated by a desire to find out whether gadget exposure in elementary school students has a relationship with diet, whether gadget exposure in elementary school students has a relationship with memory, and whether gadget exposure in elementary school students has a relationship with their physical activity. By using a quantitative correlation approach that seeks to ascertain the degree of relationship between variables. Random sample selection with the number of samples used as many as 62 fifth graders from SDN Kludan were selected to participate in this study. The data were collected using smartphone addiction index-short version (SAS-SV), semiquantitative food frequency questionnaire (SQ-FFQ), Digit span test, and Physical activity questionnaire for older children (PAQ-C). The results of the study explain that there is a significant relationship between exposure to gadgets with diet evidenced by the significant value of 0.000<0.05, and there is no significant relationship between exposure to gadgets with memory and physical activity with significant values of 0.124>0.05 and 0.157>0.05.